Pengaruh Diklat dan Pengembangan Karier Terhadap Kinerja Pegawai Perempuan; Studi di Pemerintah Kota Bandar Lampung - FaridaÂ , Ida (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2012)
The opportunity of women employees to continue their education to higher level is often hampered by internal organizational problems and family problem, as well as opportunities for training, in addition, career development for women employees is also not so smooth as copared to men employees. In this case , the performance of women employees can be better with balancing formal education, training and career development of women employees. The research method used in this research is explanatory survey. This method is used because the researcher does not only describe the empirical facts that existed in the field, but also analyze and explain the influence between variables, which include analysis of the influence of formal education , training and career development of female employee performance , through hypothesis testing. The results indicate that there is significant effect of Formal Education, Training and Career Development on Women Employee Performance. The biggest influence of these variables is the variable of formal education, while the smallest effect is the career development. Based on this research, the findings from this study is that the biggest influence on the performance of women employees within the Government of Bandar Lampung is related to the factor of formal education, namely to increase employee awareness to attend the step by step and continuous formal education, so as to create a fair opportunities between men and women employees. In fact, female employees have the same professionalism with men, although the extent of women employees is more easily challenged by their personal features.